Peran Film Dokumenter Sebagai Alat Edukasi Terhadap Dampak Kebijakan Pembangunan yang Merusak Lingkungan - Agung Widodo; Iwan Koswara; Priyo Subekti (ManBiz: Journal of Management and Business, 2025)
This study was conducted with the aim of analyzing how a documentary film can be used as an educational and advocacy tool for the community regarding the impact of development policies on environmental aspects. This study focuses on a documentary film entitled "LautAntropogenik" which raises the issue of coral reef damage on Pramuka Island, Seribu Islands Regency, DKI Jakarta Province. The damage caused by anthropogenic, especially the construction of breakwaters, is strongly visualized to clarify the impact of damage that is difficult to explain if only through written data. This study was conducted using qualitative methods and a descriptive approach implemented through data collection techniques through field observations and interviews. The results of the study revealed that documentary films have a significant role when used as educational materials. Several elements in the film such as stories of community experiences, visualization of environmental impacts, interviews with expert sources, visual statistical data, and the use of music or sound effects can help the community understand the issues being presented. However, to get more effective results, documentary films in their production need to improve the quality of production both in terms of technical production and the content of the story being presented. This study also recommends efforts to distribute films massively through platforms digital, film festivals and programs in formal education. With the right strategy, documentary films have great potential to become an effective media to encourage public awareness and behavioral change in responding to the impacts of development that damage the environment.